1994
DOI: 10.1107/s0108270193013629
|View full text |Cite
|
Sign up to set email alerts
|

[2,6-Bis(2-pyrimidinylthiomethyl)pyridine]dichlorocopper(II) methanol solvate

Abstract: Lists of structure factors, anisotropic displacement parameters, H-atom coordinates and complete geometry have been deposited with the IUCr (Reference: SH1090). Copies may be obtained through The Managing Editor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…2-8 This type of ligands can be produced by a central pyridine ring bonded to two thioether-containing arms. This coordinating unit is responsible for the formation of complexes with different metals, principally with Cu, Ni, Pd, and Pt 7 and to much less extent with Fe . We have recently shown the singular coordinating ability of NS 2 ( S -aryl) ligands incorporating the moiety 2,6-bis(thiomethyl)pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…2-8 This type of ligands can be produced by a central pyridine ring bonded to two thioether-containing arms. This coordinating unit is responsible for the formation of complexes with different metals, principally with Cu, Ni, Pd, and Pt 7 and to much less extent with Fe . We have recently shown the singular coordinating ability of NS 2 ( S -aryl) ligands incorporating the moiety 2,6-bis(thiomethyl)pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years we have reported the synthesis and complexing behavior of several macrocyclic and open-chain ligands containing the NS 2 donor group which is present in the 2,6-bis(thiomethyl)pyridine unit. , In these papers we have demonstrated that some of the studied NS 2 -based macrocycles behave as neutral carriers in all-solid-state ion-selective electrodes discriminating Cu(II) from Ni(II) and Co(II) 1d. These results encouraged us to study the coordinating abilities of new macrocycles containing the 2,6-bis(thiomethyl)pyridine unit, and we have recently reported the synthesis of the phosphine containing macrocycle 6-phenyl-15-aza-6-phospha-3,9-dithiabicyclo[9,3,1]pentadeca-1(15),11,13-triene (L in Scheme ) .…”
Section: Introductionmentioning
confidence: 99%